Feasibility study on plant chili disease detection using image processing techniques - Zulkifli, Husin; Ali Yeon, Md Shakaff, Prof. Dr.; Abdul Halis, Abdul Aziz; Rohani, S. Mohamed Farook (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/